Picture-based crop insurance (PBI): Using farmers’ smartphone pictures to reduce basis risk and costs of loss verification - Ceballos, Francisco; Kramer, Berber; Mishra, Azad; Robles, Miguel; Toor, Mann S. (International Initiative for Impact Evaluation, 2020)
Farmers in India are increasingly exposed to climate change and natural disasters, causing extreme hardship. Anticipating the possibility of such calamities, farmers underinvest in productivity-enhancing technologies. Policymakers hence seek ways to improve farmers’ resilience, and delivery of risk management strategies, including crop insurance, has become a major objective on policy agendas. Existing insurance products, however, face several challenges. On one hand, traditional indemnity insurance products suffer high transaction costs and moral hazard (Hazell, et al. 1986). On the other hand, index-based insurance, which could overcome such concerns by relying on indices that are easily measurable and outside the farmer’s control, suffer low demand due to basis risk, lack of trust, and poor product ownership (Cole et al. 2013). The study was conducted in Haryana and Punjab, two states in northwest India. These two states are the second and third largest wheat producing states in India and the largest contributors to the central pool of food grains used to provide welfare entitlements to India’s poor. Farmers in these states also have higher agricultural incomes and larger landholding sizes compared to the rest of India (Government of India 2016). However, in the last decade, yield-growth has stagnated and farmers have struggled with depleted water tables and poor soil fertility (Ministry of Agriculture and Farmer’s Welfare 2015–2016).